2016
DOI: 10.15361/1984-5529.2016v44n4p615-622
|View full text |Cite
|
Sign up to set email alerts
|

Sources and rates of residual phosphorus for Marandu palisadegrass grown in Western São Paulo

Abstract: The pastures of western São Paulo are grown on low fertility soils, therefore, forage has low nutritional value resulting low dry matter yield (DMY).Thus, phosphorus fertilization and analysis of its residual are important for livestock, as it interferes the development speed of forage grasses, allowing better use of area and helping to pasture maintenance, in addition maintaining DMY at adequate levels. This study aimed at evaluating the effect of sources and rates of phosphorus applied in Marandu palisadegra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…NDF and crude protein were determined as described by Silva et al (2009). Nitrogen concentration in shoot tissue (shoot N content) was determined by acid digestion (sulfuric acid) using a semi micro-Kjeldahl distiller Kjeltec TM 8100 (FOSS, Denmark) (Silva et al, 2016).…”
Section: Plant Tissue Analysismentioning
confidence: 99%
“…NDF and crude protein were determined as described by Silva et al (2009). Nitrogen concentration in shoot tissue (shoot N content) was determined by acid digestion (sulfuric acid) using a semi micro-Kjeldahl distiller Kjeltec TM 8100 (FOSS, Denmark) (Silva et al, 2016).…”
Section: Plant Tissue Analysismentioning
confidence: 99%
“…One of the major problems is the extremely low levels of available phosphorus as well as the high adsorption capacity of Fe and Al oxides (Silva et al 2016), and require very high P applications to increase production (Fonseca et al, 2020, Grohskopf et al, 2019, Teles et al, 2020. Another relevant factor that the phosphate fertilizers applied to the soils, observes the rates of use of P by the plants are reduced because the adsorption mechanisms (Guedes et al, 2016), mainly in highly weathered soils (Baldotto & Velloso, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesize that the risk of a high nitrate nitrogen concentration at the following cut is higher than that at first cutting because of the combined effects of both basal and additional fertilizer. Silva et al (2016) reported that P fertilizer was found to have no effect to CP concentration in palisadegrass. No effect of P fertilizer on nitrate nitrogen concentration in palisadegrass has been reported.…”
mentioning
confidence: 99%